ASTRAPOTHERIUM FROM THE MIDDLE MIOCENE COLLÓN CURA FORMATION AND THE DECLINE OF ASTRAPOTHERES IN SOUTHERN SOUTH AMERICA (Ameghiniana, 2019)
Astrapotherium is the better-known member of the placental Order Astrapotheria. This large herbivorous inhabited the Patagonian ecosystems during Early and middle Miocene times. The genus is widely represented in the Early Miocene Santa Cruz Formation, with a dozen of nominal species, of which A. magnum and A. burmeisteri are the only ones herein considered as valid. The middle Miocene record was limited to few fragmentary remains from the Rio Frias Formation and presumably from the Collón Cura Formation, described as A. hesperinum Cabrera 1940, here interpreted as nomen vanum. Here we describe an almost complete skull with associated mandible derived from the Collón Cura Formation in the vicinities of Comallo, in Rio Negro Province (Argentina). It is largely the most complete astrapothere material from middle Miocene rocks of high latitudes, and it is referred to a new species, Astrapotherium guillei. It differs from the remaining species essentially in lacking P3, achieved convergently with the latest diverging uruguaytheriines. The astrapotheriines diversified in high latitudes during the Early Miocene, but they retained an stereotyped morphotype and became progressively less diverse, unlike their Northern counterparts (the Uruguaytheriinae). Astrapotherium guillei is the latest known Patagonian astrapothere and represents the final expression of the Astrapotheriinae´s decline.doi: 10.5710/AMGH.15.07.2019.3258